C1 Scarless gene correction in huntington's disease patient-derived induced pluripotent stem cells. (13th September 2016) - Xu, Xiaohong; Tay, Yilin; Huang, Yihui; Yoon, Su-In; Sim, Bernice; Ooi, Jolene; Utami, Kagistia Hana; Radulescu, Carola; Low, Donovan; Loh, Marie; Ginhoux, Florent; Augustine, George J; et al.
Abstract : Human induced pluripotent stem cells (hiPSCs) derived from Huntington's disease (HD) patients provide a physiologically relevant cellular platform for disease modelling and drug screening studies. However, hiPSCs reprogramed from different individuals may exhibit variability in differentiation potential and cellular phenotypes that are independent of the HTT mutation due to variations in genetic background. Thus, in order to accurately detect authentic disease phenotypes and subtle alterations in cell function in hiPSC-based models, the establishment of isogenic controls is necessary. Here we report the scarless correction of an HD iPSC line carrying an expansion of 180 CAG repeats using a CRISPR-Cas9 and piggyBac transposon-based homologous recombination approach. Our results suggest that some molecular changes and phenotypes observed in HD hiPSC models compared with non-related healthy controls in fact reflect differences in the genetic background of the respective lines rather than disease-specific mutant HTT effects. Therefore, our study provides an example of scarless correction of hiPSCs from HD patients and also demonstrates the importance of isogenic controls for disease modelling using hiPSCs.